2018
DOI: 10.13040/ijpsr.0975-8232.9(3).902-15
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Herbal medicines are in great demand in the developed as well as developing countries for primary healthcare because of their wide biological and medicinal activities, higher safety margins and lesser costs. Lawsonia inermis L. is commonly known as Henna or Mhendi and abundantly available in tropical and subtropical areas. Henna belongs to lythraceae, also known as the loosestrife family. Ancient history of India describes its diverse uses and also plays appreciable role in Ayurvedic or natural herbal medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Seed treatment with 5% NaCl resulted in higher rates of germination than scari cation with sand or water soaking. L. inermis have been high in demand due to medicinal and commercial uses (Ponugoti 2018). The present study describes an attempt to develop an in vitro protocol for mass multiplication of L. inermis by manipulating the nutrient salts, growth regulators and culture conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seed treatment with 5% NaCl resulted in higher rates of germination than scari cation with sand or water soaking. L. inermis have been high in demand due to medicinal and commercial uses (Ponugoti 2018). The present study describes an attempt to develop an in vitro protocol for mass multiplication of L. inermis by manipulating the nutrient salts, growth regulators and culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…According to the records of World Health Organization, 2003, it was revealed that, nearly 80% of the population of developing countries, cannot produce their required medication and primarily depend on plant-based medicines (Chaudhary, et al 2010). Among the many medicinal plants used, Lawsonia inermis L., or Henna, has been reported to be useful both medicinally and commercially (Ponugoti, 2018). Lawsonia inermis L. leaves are the source of the dye henna, used to dye skin and fabrics.…”
Section: Introductionmentioning
confidence: 99%